Association between dietary niacin and retinal nerve fibre layer thickness in healthy eyes of different ages. (13th June 2022) - Charng, Jason; Ansari, Abdus Samad; Bondonno, Nicola P.; Hunter, Michael L.; O'Sullivan, Therese A.; Louca, Panayiotis; Hammond, Chris J.; Mackey, David A.
Abstract: Background: To investigate the relationship between dietary intake of niacin (water‐soluble form of vitamin B3 ) and retinal nerve fibre layer (RNFL) thickness in healthy eyes. Methods: This cross‐sectional study examined the association between daily niacin intake and RNFL thickness in three large population‐based cohorts with varied age differences. RNFL thickness was extracted from optical coherence tomography data; energy‐adjusted niacin intake was estimated from food frequency questionnaires. Linear mixed‐effects models were utilised to examine the association between RNFL thickness and energy‐adjusted niacin intake. Three separate analyses were conducted, with niacin treated as a continuous, a categorical (quartiles) or a dichotomous (above/below Australian recommended daily intake) variable. Results: In total, 4937 subjects were included in the study [Raine Study Gen2, n  = 1204, median age 20; Busselton Healthy Ageing Study (BHAS), n  = 1791, median age 64; TwinsUK, n  = 1942, median age 64). When analysed as a continuous variable, there was no association between RNFL thickness and niacin intake in any of the three cohorts (95% CI β: Raine Study Gen 2, −0.174 to 0.074; BHAS, −0.066 to 0.078; TwinsUK −0.435 to 0.350). Similar findings were observed with quartiles of niacin intake and for niacin intakes above or below Australian recommended daily intake levels in all three cohorts. Conclusions: Dietary intake of niacin from a standard diet does not appear to be associated with age‐related RNFL thinning in healthy eyes. Supraphysiological doses of niacin may be required for therapeutic effect in the retina.